2015
DOI: 10.1038/nature15511
|View full text |Cite
|
Sign up to set email alerts
|

Two independent and primitive envelopes of the bilobate nucleus of comet 67P

Abstract: The factors shaping cometary nuclei are still largely unknown, but could be the result of concurrent effects of evolutionary and primordial processes. The peculiar bilobed shape of comet 67P/Churyumov-Gerasimenko may be the result of the fusion of two objects that were once separate or the result of a localized excavation by outgassing at the interface between the two lobes. Here we report that the comet's major lobe is enveloped by a nearly continuous set of strata, up to 650 metres thick, which are independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
92
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 21 publications
19
92
2
Order By: Relevance
“…We recognized fractures in the Abydos region that suggest a brittle nature of the outcropping material and that often cut across strata heads. The evidence of these parallel linear features in the region agrees with the scenario that stratification is a dominant structural aspect of 67P throughout its entire bilobed shape (Massironi et al 2015). As explained in Massironi et al (2015), the comet stratification shows that the two lobes are the expression of two independent objects, perhaps formed as pebble-pile planetesimals, that are evidently characterized by onion-like stratification that is several hundred meters thick.…”
Section: Discussionsupporting
confidence: 71%
“…We recognized fractures in the Abydos region that suggest a brittle nature of the outcropping material and that often cut across strata heads. The evidence of these parallel linear features in the region agrees with the scenario that stratification is a dominant structural aspect of 67P throughout its entire bilobed shape (Massironi et al 2015). As explained in Massironi et al (2015), the comet stratification shows that the two lobes are the expression of two independent objects, perhaps formed as pebble-pile planetesimals, that are evidently characterized by onion-like stratification that is several hundred meters thick.…”
Section: Discussionsupporting
confidence: 71%
“…Sierks et al 2015;Hässig et al 2015;Capaccioni et al 2015). Based on this data, it has been suggested that its structure is pristine and was formed in the early stages of the solar system (Massironi et al 2015), possibly by low velocity accretionary collisions (Jutzi & Asphaug 2015). What is less clear is whether or not a structure like comet 67P would have been able to survive until today.…”
Section: Introductionmentioning
confidence: 99%
“…In the first report of the OSIRIS science imaging results, Sierks et al (2015) suggested that the nucleus of 67P/Churyumov-Gerasimenko (67P hereafter) could be just one single monolith (see also Thomas et al 2015). Subsequently, Massironi et al (2015), showed that a contact binary model with the two lobes being completely different entities or cometesimals could be an explanation (see also Rickman et al 2015;Davidsson et al 2016;El-Maarry et al 2015a). Similar scenarios may be proposed for the dumb-bell shaped structures of comet 103P/Hartley 2, comet 1P/Halley and comet 19P/Borrelly even though the shapes of comet 9P/Tempel 1 and 81P/Wild 2 are certainly more monolithic.…”
Section: Introductionmentioning
confidence: 99%